Characterization of cmcp Gene as a Pathogenicity Factor of Ceratocystis manginecans - Zhang, Zhiping; Li, Yingbin; Luo, Laixin; Hao, Jianjun; Li, Jianqiang (Frontiers in Microbiology, 2020)
Ceratocystis manginecans causes mango wilt with significant economic losses. In the infection court, cerato-platanin (CP) family proteins (CPPs) are believed to involve in pathogenesis but has not been determined in C. manginecans. To confirm this function, a CP protein (CmCP) of C. manginecans was characterized in this study. A protoplast of C. manginecans was prepared by treating its mycelia with driselase and lysing enzymes. The cmcp gene was edited using CRISPR/Cas-U6-1 expression vectors in 60% PEG and 50 μg/mL hygromycin B in the medium, resulting in mutants with cmcp deletion (∆cmcp). A complimented mutant (∆cmcp-C) was obtained by transforming cmcp to ∆cmcp. Both ∆cmcp and ∆cmcp-C were characterized by comparing them with a wild-type strain on morphology, mycelial growth, conidial production and pathogenicity. Additionally, cmcp was transformed and expressed in Pichia pastoris, and the derived recombinant protein CmCP caused a severe necrosis on Nicotiana tabacum leaves. CmCP-treated plant leaves showed symptoms of hypersensitive response including electrolyte leakage, reactive oxygen species generation and overexpression of defense-related genes PR-1, PAD3, ERF1, HSR203J and HIN1. All those results suggested that cmcp gene was required for the growth development of C. manginecans and functioned as a major pathogenicity factor in mango infection.